From squatter settlements to cultural heritage: the preservation and revitalization as "group of buildings" based on the case experience of Treasure Hill Art Village in Taipei City, Taiwan. Issue 2 (4th March 2022) - Hsiao, Hongwei
ABSTRACT: This paper focuses on the value of squatter settlements (SS) as cultural heritage, which has not been fully addressed. This paper aims at arguing the possibility of utilizing the value of cultural heritage embedded in SS as an art incubator under community participation through a case analysis based on the experience of the Treasure Hill Art Village (THAV) of Treasure Hill Settlement (THS) in Taipei City, Taiwan. This paper clarifies the significance of SS as "a group of buildings" realized by the process of preservation, legalization, and revitalization by way of community participation. THS can be evaluated as a unique case from the perspective of the preservation and legalization processes because it might be considered a mixed type of "legalization of the ownership of buildings and land" and "legalization of residence rights of residents" of SS. Focus on the revitalization of THAV has many spatial characteristics because of the restoration transcending the mere maintenance of its intrinsic value. Further, community participation has evolved to be stronger during the process of preservation and revitalization of THS as THAV. The possibility of how SS may become an irreplaceable space to the city by dynamically revitalizing its value has been clarified by THAV. Graphical Abstract: uf0001